An Investigation of Stationarity Properties of the Turkish Tourism Income Variable - H. M. Ertugrul; S. Yildirim; F. Ayhan (International Econometric Review (IER), 2017)
Tourism has a significant impact on economic growth as put forth by the tourism-led growth hypothesis. Turkey's earnings from tourism were 31.5 billion dollars in 2015 according to TURKSTAT. This implies that tourism is an important industry for Turkey and has a significant impact on economy. Therefore, the question whether a policy implementation in tourism is long-lasting or not is critical for both the industry and whole economy. This study researches the persistence of policies in tourism industry, employing tourism income series for period of 2009M1-2015M12 and tests the stationarity of this series using traditional unit root tests as well as a wavelet-based unit root test developed by Fan and Gencay (2010). Both seasonally adjusted and unadjusted series have been used. The empirical results point out that the traditional unit root test has a proclivity to report that tourism income series is I(1) or non-stationary. On the other hand, the wavelet-base unit root test indicates that tourism income is stationary. The empirical result of wavelet-based test implies that impact of a shock on this sector is transitory. The income in tourism industry will return more or less back to its meaning the following year.
Keywords: F43; L83; O47; 330; Tourism Income; Unit Root; Wavelet; Stationarity Analysis